2014
DOI: 10.5897/jdae2013.0516
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of operational aspects of the input supply chain under national agriculture input voucher scheme (NAIVS) in Tanzania

Abstract: based on secondary and primary data. Primary data were collected from a random sample of 300 households in four regions namely: Rukwa, Mbeya, Morogoro and Shinyanga. Secondary data were collected from the Ministry of Agriculture Food Security and Cooperatives (MAFC), Agro dealers and Local Government Authorities. Results indicate that 88% of farmers reported delayed subsidized inputs significant at p = 0.05. The inputs become available during planting season when most of the household food stocks and income is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
1
6
1
Order By: Relevance
“…Other studies on sub-Saharan Africa such as by Jayne et al (2018) found a similar effect, unlike Asia where there was an increase in production and welfare in both the short and long run in rural areas (Bathla et al 2019;Solaymani et al 2019;Zhang et al 2020). However, this is contrary to the findings of some studies of Tanzania, such as those by Aloyce et al (2014), Gine et al (2019), andKato (2016), which found that NAIVS had no impact on agriculture production.…”
Section: Psm Estimations For the 2008-13 Periodcontrasting
confidence: 99%
See 2 more Smart Citations
“…Other studies on sub-Saharan Africa such as by Jayne et al (2018) found a similar effect, unlike Asia where there was an increase in production and welfare in both the short and long run in rural areas (Bathla et al 2019;Solaymani et al 2019;Zhang et al 2020). However, this is contrary to the findings of some studies of Tanzania, such as those by Aloyce et al (2014), Gine et al (2019), andKato (2016), which found that NAIVS had no impact on agriculture production.…”
Section: Psm Estimations For the 2008-13 Periodcontrasting
confidence: 99%
“…On the other hand, Aloyce et al (2014) reported that delays in input subsidies made the vouchers ineffectual since, by the time of receipt, households had already spent most of their earnings on food and, therefore, they could not afford the 50 per cent top-up. The authors attributed this to poor monitoring and evaluation systems.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield in villages with electricity was slightly higher than in villages without electricity during both waves. The yield trends of major food crops in Tanzania has been mixed; some researchers reporting improvement during the subsidy programme (Ray, 2019) while others reported the subsidy had little impact on yields due to poor targeting and management (Aloyce, et al 2014;Kato, 2007;Kinuthia 2020). The combined effect of decline in yield due to the decline in area under rice (Table 4) and reduction in inputs use (Table 6) led to a general decline in total volume of paddy harvested per household between the twoyear interval (Figure 1) for all farmer categories except medium scale farmers whose total harvest increased, benefiting from area expansion as reported earlier.…”
Section: Changes In Use Of Inputs and Productivitymentioning
confidence: 99%
“…The majority of the studies on fertilizer policy in Nigeria have been focused on agricultural development in the economy and hence, better farmers' welfare. Such studies by (Coker, 2014) studied the effect of fertilizer policy on crop production in Nigeria; (Eboh, Ujah and Amaechina 2006;Aloyce et al, 2014) studied how government fertilizer subsidies benefit rural farmers in Nigeria. Making sense out of existing data; Nagy and Edun (2002) assessed Nigerian government fertilizer policy and suggested alternative market-friendly policies.…”
Section: Issues Militating Against Nigeria Fertilizer Sectormentioning
confidence: 99%